Quantitative methods in magnetization transfer and chemical exchange saturation transfer at 7T - Geades, Nicolas (2017)
Ultra-High field (7T) MRI provides high sensitivity which allows for new qualitative and quantitative methodologies to be developed, that provide clinically useful information. The work presented in this thesis is focussed on developing a quick and reliable quantitative MT and CEST methodology, taking account of the difficulties encountered at high field. The method developed here has been tested on various studies, in both healthy and diseased brain, in an effort to aid the understanding of myelination in the human brain.